2004
DOI: 10.1093/annonc/mdh092
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of MCC-465, a doxorubicin (DXR) encapsulated in PEG immunoliposome, in patients with metastatic stomach cancer

Abstract: MCC-465 was well tolerated. The recommended dose for a phase II study of MCC-465, for a 3-week schedule, is considered to be 32.5 mg/m2 in an equivalent amount of DXR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(84 citation statements)
references
References 10 publications
0
80
0
2
Order By: Relevance
“…With respect to immunoliposomes, although many preclinical studies can be found in the literature [24,215,275,276] and a few clinical trials are in progress [18,75,[277][278][279] an siRNA that targets PKN3 [18,286], or TKM-PLK1 that includes siRNA against PLK1 for the treatment of neuroendocrine tumors and adrenocortical carcinomas (phase I/II clinical trials) [283,287,288]. The phase I liposomic formulation SGT-53 includes plasmidic DNA that expresses the tumor suppressor gene p53 to treat solid tumors [280,289].…”
Section: Nl Cpt-11mentioning
confidence: 99%
“…With respect to immunoliposomes, although many preclinical studies can be found in the literature [24,215,275,276] and a few clinical trials are in progress [18,75,[277][278][279] an siRNA that targets PKN3 [18,286], or TKM-PLK1 that includes siRNA against PLK1 for the treatment of neuroendocrine tumors and adrenocortical carcinomas (phase I/II clinical trials) [283,287,288]. The phase I liposomic formulation SGT-53 includes plasmidic DNA that expresses the tumor suppressor gene p53 to treat solid tumors [280,289].…”
Section: Nl Cpt-11mentioning
confidence: 99%
“…66,67) Incorporation of EGF into PEGylated nanoparticles was also demonstrated for targeting to the EGF-R. [68][69][70] other molecules overexpressed on tumors such as nucleosome, cd19, membrane type 1 matrix metalloproteinase (MT1-MMP), GAH, Gd2, and heparinbinding EGF-like growth factor were targeted by immunoliposomes. [71][72][73][74][75][76][77] Aptamers are single-stranded dNA or RNA, can specifically bind molecules, and are beginning to be used as targeting ligands for drug delivery systems. [78][79][80][81] Peptides containing specific motifs in sequence which recognize specific molecules have been identified using phage-displayed peptide libraries.…”
Section: -28)mentioning
confidence: 99%
“…For example, anti-EGFR immunoliposomes encapsulating DOX have been shown to target the epidermal growth factor receptor by coupling Fab′ fragments of the Cetuximab monoclonal antibody on the surface of the liposomes [96,97]. MCC-465 is a PEGylated immunoliposome containing DOX, modified with the F(ab')2 fragment of GAH human monoclonal antibody, for the treatment of gastric cancer [97,98]. The delivery of DOX to the brain via liposomes has been enhanced by conjugation with glutathione.…”
Section: Clinical Experience With Liposomes For Cancer Chemotherapymentioning
confidence: 99%